2018
DOI: 10.1186/s40478-018-0514-4
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes taken up by neurons hijack the endosomal pathway to spread to interconnected neurons

Abstract: In Alzheimer disease and related disorders, the microtubule-associated protein tau aggregates and forms cytoplasmic lesions that impair neuronal physiology at many levels. In addition to affecting the host neuron, tau aggregates also spread to neighboring, recipient cells where the misfolded tau aggregates, in a manner similar to prions, actively corrupt the proper folding of soluble tau, and thereby impair cellular functions. One vehicle for the transmission of tau aggregates are secretory nanovesicles known … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
145
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(154 citation statements)
references
References 67 publications
9
145
0
Order By: Relevance
“…EVs are involved in the extracellular enzymatic degradation of Aβ and are shown to promote Aβ aggregation and clearance by microglia [16,17]. On other hand, several researchers have reported the models of neuron-to-neuron transfer of tau seeds by EVs [12,[18][19][20]. Previous work in our lab has shown that microglia spread tau via EV secretion, and that inhibiting EV synthesis significantly reduced tau propagation in vitro and in vivo [10].…”
Section: Introductionmentioning
confidence: 92%
“…EVs are involved in the extracellular enzymatic degradation of Aβ and are shown to promote Aβ aggregation and clearance by microglia [16,17]. On other hand, several researchers have reported the models of neuron-to-neuron transfer of tau seeds by EVs [12,[18][19][20]. Previous work in our lab has shown that microglia spread tau via EV secretion, and that inhibiting EV synthesis significantly reduced tau propagation in vitro and in vivo [10].…”
Section: Introductionmentioning
confidence: 92%
“…Macropinocytosis and HSPGs may also be responsible for the uptake of whole exosomes [196], although it is possible that exosomes are internalized as a result of the unspecificity of micropinocytosis. In general, endocytosis and/or pinocytosis has been reported to be a favored internalization route for exosomes over direct fusion to the PM [197,198].…”
Section: Cellular Uptake and Templated Misfolding Of Tau In Recipientmentioning
confidence: 99%
“…The exact mechanism of transmission is not known. Release and trans-synaptic transmission of tau [164,165], tau uptake via exosomes [166][167][168] or nanotubules [169] and free uptake of fibrillar proteins [170,171] have all been suggested as putative mechanisms using cultured neurons. Although astrocyte-to-neuron intercellular transfer mediated by cell-to-cell contact has been postulated for prions [172], no information is available concerning astrocyte-to-neuron transfer in tauopathies.…”
Section: Disease Progression: Seeding and Spreading; Role Of Astrocytesmentioning
confidence: 99%